1995
DOI: 10.1259/0007-1285-68-815-1212
|View full text |Cite
|
Sign up to set email alerts
|

Broadband ultrasonic attenuation: are current measurement techniques inherently inaccurate?

Abstract: Measurements of broadband ultrasonic attenuation (BUA) are currently made using large aperture, piezoelectric transducers. The use of such a receiver is known to lead to the possibility of an overestimate of ultrasonic attenuation due to phase cancellation and it is shown theoretically that this same effect can also lead to an overestimate of BUA. Using a new scanning approach, BUA was measured using two methods, one sensitive to the phase of the acoustic wave, the other not. The phase sensitive BUA measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 2 publications
0
27
1
Order By: Relevance
“…Indeed, when compared to the young, trabecular number is decreased and trabecular spacing increased in the elderly osteoporotic [27]. Higher BMD in the young may thus lead to greater 'phase cancellation' and exaggerated ultrasound attenuation [53], accentuating the discordance observed in correlation coefficients of QUS and BMD with age.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when compared to the young, trabecular number is decreased and trabecular spacing increased in the elderly osteoporotic [27]. Higher BMD in the young may thus lead to greater 'phase cancellation' and exaggerated ultrasound attenuation [53], accentuating the discordance observed in correlation coefficients of QUS and BMD with age.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Quantitative ultrasound parameters, such as speed of sound and broadband ultrasonic attenuation ͑BUA͒, have been shown to correlate with bone mineral density ͑BMD͒.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have addressed these issues in bone, and have demonstrated the artifacts inherent in phase sensitive measurements. 20,24,25 …”
Section: Introductionmentioning
confidence: 99%